DESIGN OF PROTOTYPE DEVELOPMENT ON LECTURER PRESENCE SYSTEM INTEGRATION AT IBI DARMAJAYA - Nurfiana, Nurfiana; Kurniawan, Hendra (Prosiding International conference on Information Technology and Business (ICITB), 2016)
ABSTRAKÂ The design of Prototype development on lecturer presence system integration at IBI Darmajaya is a study used to monitor lecturerâs teaching activities based on days, hours, classrooms, and specific subjects based on the schedule made previously and results in up-to-date information on the lecturerâs teaching.The lecturer presence process at IBI Darmajaya has been using a presence application; the monitoring process on the record of lecturerâs teaching presence data becomes the responsibility of the official/ the Pusat Layanan Pelaporan Perkuliahan (PLPP) staffs for inputting the data into that application. This surely gives impacts on the performance of the PLPP department when there are teaching queues at specific hours and there is also inefficiency and inconsistency in recording the lecturerâs teaching presence. The result of this study is a Prototype of lecturer presence system integration with centralized database placed in each classroom/ laboratory in which it demands the lecturers individually to do the teaching presence at every lecture.Â Key Words:Â lecturer presence,prototypeof lecturer presence, lecturer presence integration